Pendampingan Peningkatan Potensi Objek Retribusi Daerah Melalui IMB di Distrik Tanah Miring dan Semangga Kabupaten Merauke - Raubaba, Henry Soleman; Alahudin, Muchlis (Fakultas Peternakan Universitas Papua, 2020)
ABSTRACT Increasing the potential of regional retribution objects in the Merauke Regency is an effort of the regional government to increase regional budget revenues. Izin Mendirikan Bangunan (IMB) or the